A study of cognitive impairment and its neuroimaging correlates in patients with alcohol dependence a cross-sectional study - Kandasamy V; Abdul Rahuman MB; Ramanujam G (Asian Journal of Medical Sciences, 2023)
Background: Alcohol abuse is one of the most common psychiatric disorders observed worldwide. Aims and Objectives: The study aimed to assess cognitive impairment in alcohol-dependent patients, its correlation with neuroimaging, and compare the findings with non-alcoholics. Materials and Methods: We have included 30 alcoholics and 30 control participants. Tools such as semi-structured pro forma, alcohol use disorder identification test score, the severity of alcohol dependence questionnaire (SADQ), and PGI memory scale (PGIMS) were used for the assessment. The measurements of the third and fourth ventricle width, interhemispheric fissure width, cerebellar transverse width, the inner diameter of the skull, anterior horn distance, and midbrain diameter were taken from a magnetic resonance imaging (MRI) brain. Results: There was a significant difference in remote memory, mental balance, attention and concentration, delayed recall, immediate recall, visual retention, third and fourth ventricle width, interhemispheric fissure width, and cerebral transverse length between alcoholics and non-alcoholics. Further, a correlation analysis of the PGIMS total score with MRI measurements and alcohol intake showed a significant negative correlation of PGIMS total score with third ventricle width, duration of alcohol consumption, period of alcohol dependence, the quantity of alcohol per day, and SADQ score. However, a significantly positive correlation was observed between PGIMS total score and cerebellar transverse length. Conclusion: Alcohol-dependent patients had poor cognitive functions compared to non-alcoholics. They also had significant cerebral and cerebellar atrophy and were characterized by dilation of the third and fourth ventricles. The increase in the duration of alcohol consumption, period of alcohol dependence, and quantity of alcohol intake caused cognitive impairment independently.